CARDIOVASCULAR EFFECTS OF FREE OR COMPLEXED LINALOOL WITH Β-CYCLODEXTRIN: A FOCUS FOR ANTIHYPERTENSIVE ACTION - Pedreira, Jordana Clara Gomes; Filho, Edward Rodrigues de Oliveira; Pereira, Héllida Patrícia Oliveira Camilo; Martins, Anderson Felipe Caixêta; Schoepfer, Felipe Dayrell; Nogueira, Rafaella Ribeiro Gomes; Oliveira, Jim Davis de; Pimentel, Herik Jansen de Souza; Mendonça, Josiely Anelise; Costa, Paulo Otávio Magalhães; Guimarães , Nara Márcia Amaro Domingos; Guimarães, Vinícius (Brazilian Journal of Implantology and Health Sciences, 2024)
Investigating the cardiovascular effects of natural compounds, such as linalool, has aroused interest due to the potential impact on cardiovascular health. Linalool, a component present in several essential oils, has demonstrated promising pharmacological properties, including antihypertensive activity. However, its bioavailability and efficacy can be influenced by complexation with β-cyclodextrin, a strategy frequently used to improve the solubility and stability of bioactive substances. This study aimed to carry out a systematic review of the literature, exploring the cardiovascular effects of free linalool and linalool complexed with β-cyclodextrin. Objective: To investigate the cardiovascular effects of free linalool and linalool complexed with β-cyclodextrin, with emphasis on the antihypertensive action, through a systematic review of the literature. Methodology: The review was conducted according to PRISMA guidelines. The PubMed, Scielo and Web of Science databases were consulted, using the descriptors "linalool", "β-cyclodextrin", "cardiovascular effects", "antihypertensive" and "complexation". The inclusion criteria covered studies published in the last 10 years, focusing on in vivo experiments, clinical trials and systematic reviews. Articles unrelated to the topic, duplicate studies and those without peer review were excluded. Results: They revealed that linalool, when complexed with β-cyclodextrin, presented greater bioavailability and stability, enhancing its antihypertensive action. In vivo studies have demonstrated a significant reduction in blood pressure in hypertensive animal models. Furthermore, the complexation positively influenced the gastrointestinal absorption of linalool. These findings suggest that the complexed formulation may represent an effective approach to improving the cardiovascular effects of linalool. Conclusion: The systematic review highlights the relevance of complexing linalool to β-cyclodextrin as a strategy to enhance its antihypertensive effects. Understanding these mechanisms can contribute to the development of more effective pharmaceutical formulations in the management of hypertension, promoting advances in cardiovascular therapy.